2019
DOI: 10.3389/fphar.2019.00535
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhetinic Acid Maintains Intestinal Homeostasis via HuR

Abstract: Glycyrrhetinic acid (GA) is one of the main components of the traditional Chinese medicine of licorice, which can coordinate and promote the effects of other medicines in the traditional prescription. We found that GA could promote the proliferation, decrease the apoptotic rate, and attenuate DFMO-elicited growth arrest and delay in restitution after wounding in IEC-6 cells via HuR. GA failed to promote proliferation and to suppress apoptosis after silencing HuR by siRNA in IEC-6 cells. Furthermore, with the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Probiotics may also help boost the proliferation of crypt cells in the small intestine ( He et al., 2019 ). Furthermore, Galla Chinensis, Arctii Fructus, and Glycyrrhizae Radix contained in the CPCMP have some active ingredients, such as gallic acid ( Samuel et al., 2017 ), pectin ( Li et al., 2019 ), and glycyrrhetinic acid ( Chen et al., 2019 ), which can positively modulate the intestinal morphology and function. It is speculated that the aforementioned effects of CPCMP on intestinal morphology may be related to the combined action of probiotics and TCMs.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics may also help boost the proliferation of crypt cells in the small intestine ( He et al., 2019 ). Furthermore, Galla Chinensis, Arctii Fructus, and Glycyrrhizae Radix contained in the CPCMP have some active ingredients, such as gallic acid ( Samuel et al., 2017 ), pectin ( Li et al., 2019 ), and glycyrrhetinic acid ( Chen et al., 2019 ), which can positively modulate the intestinal morphology and function. It is speculated that the aforementioned effects of CPCMP on intestinal morphology may be related to the combined action of probiotics and TCMs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that small-molecular food phytochemicals such as glycyrrhetinic acid and polydatin can protect intestinal epithelium [ 208 , 267 ]. Therefore, there is an urgent need to summarize the detailed effect of foods on intestinal aliments at different stages.…”
Section: Other Foods That Can Potentially Help Treat Leaky Gutmentioning
confidence: 99%
“…As previously reported, organoid models have been used to evaluate the protective effect of TCM on intestinal damage (Glycyrrhetinic acid from Glycyrrhiza uralensis Fisch. ), 93 cancer (Gambogic acid from Garcinia hamburgy Hook. f.), 94 regeneration of intestinal epithelia ( Trillium tschonoskii ) 95 and so on.…”
Section: The Classical Experimental Model Of the Anti‐inflammatory Ef...mentioning
confidence: 99%